We can't mitigate what we don't monitor: using informatics to measure and improve healthcare systems' climate impact and environmental footprint. (12th July 2022) - Smith, Carolynn L; Zurynski, Yvonne; Braithwaite, Jeffrey
Abstract: Climate change, human health, and healthcare systems are inextricably linked. As the climate warms due to greenhouse gas (GHG) emissions, extreme weather events, such as floods, fires, and heatwaves, will drive up demand for healthcare. Delivering healthcare also contributes to climate change, accounting for ∼5% of the global carbon emissions. To rein in healthcare's carbon footprint, clinicians and health policy makers must be able to measure the GHG contributions of healthcare systems and clinical practices. Herein, we scope potential informatics solutions to monitor the carbon footprint of healthcare systems and to support climate-change decision-making for clinicians, and healthcare policy makers. We discuss the importance of methods and tools that can link environmental, economic, and healthcare data, and outline challenges to the sustainability of monitoring efforts. A greater understanding of these connections will only be possible through further development and usage of models and tools that integrate diverse data sources.